Majaz dalam al-Quran: Refleksi atas Persoalan Linguistik / Majaz in the Koran: Reflection on Linguistic issues / Al-Majaz fi al-Qur’an: Al-Taammul fi Qadhaya Lughawiyah - Fattah, Abd; Hamzah, Hamzah; Djuaeni, M. Napis; Hamid, M. Abdul (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Secara historis, tidak semua ulama menerima keberadaan makna majazi dalam al-Quran. Hal tersebut menjadi suatu hal kontroversial dikalangan para ulama bahasa dan mufassir dengan dalih masing-masing. Penelitian ini bertujuan untuk merefleksikan persoalan linguistik terhadap makna majazi dalam al-Qurán dengan sub bahasan terminologi majaz dan klasifikasinya dalam ilmu Balaghah, pro-kontra eksistensi majaz dalam al-Quran, dan contoh kalimat majazi dalam al-Quran. Penelitian ini termasuk dalam penelitian deskriptif kualitatif yang desainnya termasuk studi pustaka sebab data-datanya berasal dari berbagai referensi pustaka baik berbentuk buku maupun artikel ilmiah. Pengumpulan datanya dilakukan lewat teknik dokumentasi, dan analisis datanya menggunakan model interaktif lewat kondensasi data baik secara induktif maupun deduktif berdasarkan kebutuhan penelitian setelah data dikumpulkan, penyajian data, verifikasi dan penarikan kesimpulan. Adapun hasil penelitian ini adalah majaz dalam bahasa Arab sudah teradaptasi ke dalam bahasa Indonesai dengan adaptasi bunyi majas yang sama-sama bermakna kiasan. Terkait klasifikasi majaz dalam ilmu Balaghah secara garis besar terbagi dua yaitu majaz ‘aqliy dan majaz lughawi, dari dua jenis inilah yang melahirkan banyak ragam jenis majaz yang secara keseluruhan berjumlah 18 macam berdasarkan tinjauannya masing-masing. Persoalan majaz atau makna majazi dalam al-Quran menjadi kontroversial di kalangan tiga aliran besar, yaitu: aliran Muktazilah yang pro, aliran Zahiriyah yang kontra, dan aliran Asyariyah yang moderat. Ayat-ayat Al-Qur’an yang memuat makna majazi, yaitu Q.S. al-An’am/6:6., Q.S. al-Haqqah/69:13., Q.S. al-Isra’/17:45. Q.S. al-Rahman/55:27., Q.S. al-Baqarah/2:19., Q.S. al-Mu’min/13:11., Q.S. al-Nisa’/4:2., Q.S. Yusuf/12:36., Q.S. Ali ‘Imran/3:107., Q.S. Maryam/6:50., Q.S. al-Nisa’/4:54., Q.S. Ali ‘Imran/3:173., Q.S. al-Nisa’/4:103., Q.S. al-Naml/27:88., Q.S. al-Waqi’ah/56:2., Q.S. al-Hud/11:43., Q.S. al-Isra/17:45. Q.S. Ibrahim/14:1., Q.S. Thaha/20:71., Q.S. al-Baqarah/2:16., Q.S. al-Haqqah/69:11., Q.S. al-An’am/6:122., dan Q.S. Ali ‘Imran/3:21. AbstractHistorically, not all scholars accept the existence of the majazi meaning in the Koran. This has become a controversial matter among language scholars and interpreters with their respective pretexts. This study aims to reflect on linguistic issues regarding the meaning of majazi in the Koran by sub-discussing majaz terminology and its classification in Balaghah science, the pros and cons of the existence of majaz in the Koran, and examples of majazi sentences in the Koran. This research is included in the descriptive qualitative research whose design includes literature study because the data comes from various references both in the form of books and scientific articles. The data collection is done through documentation techniques, and the data analysis uses an interactive model through condensation of data both inductively and deductively based on research needs after the data is collected, data display, verification and drawing conclusions. The results of this study are that majaz in Arabic has been adapted into Indonesian with the adaptation of the sound of majas which both have figurative meanings. Regarding the classification of majaz in Balaghah, broadly speaking, it is divided into two, namely majaz 'aqliy and majaz lughawi, of these two types which display many different types of majaz, totaling 18 types based on their respective reviews. The issue of majaz or the meaning of majazi in the Koran has become controversial among three major streams of thought, namely: Mutazilah stream that is pro to the meaning of majazi, Zahiriyah stream that is contra, and Asyariyah stream that is moderate. The verses of the Qur'an that contain majazi meaning, namely Q.S. al-An'am/6:6., Q.S. al-Haqqah/69:13., Q.S. al-Isra'/17:45. Q.S. al-Rahman/55:27., Q.S. al-Baqarah/2:19., Q.S. al-Mu'min/13:11., Q.S. al-Nisa'/4:2., Q.S. Yusuf/12:36., Q.S. Ali 'Imran/3:107., Q.S. Maryam/6:50., Q.S. al-Nisa'/4:54., Q.S. Ali 'Imran/3:173., Q.S. al-Nisa'/4:103., Q.S. al-Naml/27:88., Q.S. al-Waqi'ah/56:2., Q.S. al-Hud/11:43., Q.S. al-Isra/17:45. Q.S. Ibrahim/14:1., Q.S. Thaha/20:71., Q.S. al-Baqarah/2:16., Q.S. al-Haqqah/69:11., Q.S. al-An'am/6:122., and Q.S. Ali 'Imran/3:21. مستخلص البحثتاريخيا، لا يقبل جميع العلماء وجود معنى المجاز في القرآن. لقد أصبح هذا موضوعا مثيرا للجدل بين علماء اللغة والمفسرين بحجج كل منهم. تهدف هذا البحث إلى التأمل في القضايا اللغوية المتعلقة بمعنى المجاز في القرآن من خلال مناقشة مصطلحات المجاز وتصنيفها في علم البلاغة، وإيجابيات وسلبيات وجود المجاز في القرآن، وأمثلة الجمل المجازية في القرآن. يعتبر هذا البحث بحثا نوعيا الوصفي الذي يتضمن تصميمه دراسة المكتبية لأن البيانات تأتي من مراجع مختلفة سواء في شكل كتب أو مقالات علمية. يتم جمع البيانات فيه من خلال تقنيات التوثيق، ويستخدم تحليل البيانات فيه نموذجا تفاعليا من خلال تكثيف البيانات استقرائيا أو استنتاجيا بناء على احتياجات البحث بعد جمع البيانات وعرض البيانات والتحقق والاستنتاج. ونتائج هذا البحث هي أن المجاز باللغة العربية قد تم تكييفها إلى اللغة الإندونيسية مع تكييف صوت